Longstanding Endobronchial Foreign Body. Issue 4 (1999) - Trisolini, R.; Dore, R.; Bertolini, R.; Pasturenzi, L.; Catania, A. Fede; Gualtieri, G.; Luisetti, M.; Torre, M.
Abstract : There are many circumstances in which the diagnosis of endobronchial inhalation of a foreign body (FB) can be missed. Generally, in such cases, within weeks or at most months from the event, clinical bronchopulmonary symptoms develop which allow a correct diagnosis to be made and significant complications to be avoided. We report the case of a patient in whom an endobronchial FB remained undiagnosed, because of lack of symptoms, for almost three years, and then caused signifiicant complications before being identified and removed. Problems related to diagnosis and therapy are discussed.